Jesus and time : an interpretation of Mark 1.15 - Palu, Ma'afu (Library of New Testament studies, 2012)
This work offers an examination of Jesus conception of time on the basis of Mark 1.15. Palu contends that the background which makes Mark 1.15 most intelligible is Gods covenant with day and night which is established in the act of creation, specified in prophetic eschatology, and developed inSecond Temple literature; it is God's commitment to give day and night in their appointed time, promising the restoration of Israel under David's offspring. On the basis of recent developments in scholarly literature concerning the Greek verbal aspect, this study argues that the perfect verbs in Mark 1.15 d.